2021
DOI: 10.3389/fpsyg.2021.705005
|View full text |Cite
|
Sign up to set email alerts
|

Proactive Personality Measurement Using Item Response Theory and Social Media Text Mining

Abstract: This prospective study was designed to propose a novel method of assessing proactive personality by combining text mining technology and Item Response Theory (IRT) to measure proactive personality more efficiently. We got freely expressed texts (essay question text dataset and social media text dataset) and item response data on the topic of proactive personality from 901 college students. To enhance validity and reliability, three different approaches were employed in the study. In Method 1, we used item resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 68 publications
(68 reference statements)
0
1
0
Order By: Relevance
“…As summarized above, our review of the literature showed that combining ML and IRT fields is one of the hot topics day by day in the fields of education, psychology, and computer science. This combination often aims to solve cold-start problem in learning ability evaluation, 28,36 classifier/instance hardness evaluation, 27,[29][30][31]33,37 suitable dataset selection, 38 estimation of IRT parameters, 32,35,39 FS, 7,[24][25][26] feature extension, 40 and other purposes especially ones 7,41,42 that use information between IRT models and text mining tasks. This brief summarization shows that using IRT models as feature selectors is also attracting the interest of the research community, especially in the field of computer science.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As summarized above, our review of the literature showed that combining ML and IRT fields is one of the hot topics day by day in the fields of education, psychology, and computer science. This combination often aims to solve cold-start problem in learning ability evaluation, 28,36 classifier/instance hardness evaluation, 27,[29][30][31]33,37 suitable dataset selection, 38 estimation of IRT parameters, 32,35,39 FS, 7,[24][25][26] feature extension, 40 and other purposes especially ones 7,41,42 that use information between IRT models and text mining tasks. This brief summarization shows that using IRT models as feature selectors is also attracting the interest of the research community, especially in the field of computer science.…”
Section: Literature Reviewmentioning
confidence: 99%